Effects of canoe ergometer training in normal and hypoxic environment in elite Canadian canoeists - Hirayama, H.; Yamamoto, M. (Journal of Training Science for Exercise and Sport, 2011)
The purpose of this study was to investigate the effects of high intensity interval training using a Canadian canoe ergometer under normal as well as hypoxic environment in national or collegiate championship level canoeists. Nine men (N; normal training group) performed high intensity interval training at sea level, whereas the other nine men (H; hypoxic training group) trained in low-oxygen environment (equivalent to 2000-3000m altitude) using a normobaric hypoxic room. The subjects performed this ergometer training for 3 or 4 days per week, over a 3 week period. This ergometer training was incorporated into their daily training in a college canoe team. After the training period, aerobic working capacity (maximal oxygen uptake), anaerobic working capacity (10-second maximal paddling power), performances at 200m and 500m time trial improved significantly in both groups. Furthermore, the improvement of 200m performance was larger in H group than N group. These results suggest that additional canoe ergometer training under normal or hypoxic environment improves both anaerobic and aerobic working capacity, and results in the improvement of 200m and 500m performance. Moreover, if the training is performed under hypoxic environment, 200m performance will improve larger than that of sea level training.